Epilepsy As A Rare Intracranial Complication of Pansinusitis: A Case Series - Samudra, Edeline; Ketaren, Retno Jayantri (Departemen Neurologi Fakultas Kedokteran Universitas Indonesia, 2026)
Introduction: Epilepsy is a condition characterized by recurrent and unpredictable seizures with an underlying mechanism that remains incompletely understood. A hallmark feature is over-synchronized neuronal discharge due to the loss of inhibitory control over glutamatergic neurons, with neuroinflammation being a potential contributing factor. Case Report: We report two cases of epilepsy in patients with a history of pansinusitis. A 14-year-old male experienced a first-onset generalized seizure, while a 23-year-old female presented with recurrent focal-to-bilateral seizures. CT scans revealed pansinusitis, predominantly affecting the bilateral frontal sinuses with bilateral ostiomeatal complex blockage in one patient, and the maxillary sinuses with an open bilateral ostiomeatal complex in the other patient. No evidence of intracranial infection or other epilepsy causes were found, suggesting epilepsy as an intracranial complication (IC) of pansinusitis. One patient was managed with medication, while the other underwent functional endoscopic sinus surgery. (FESS), revealing sinonasal polyps on histology. Discussion: ICs, including epilepsy, are rare but serious complications of pansinusitis and can lead to disabling neurological sequelae. The most common source of IC is frontal sinusitis, followed by ethmoid, sphenoid, and maxillary sinusitis. ICs occur via direct infection spread through dehiscent bone or through natural pathways, such as the olfactory foramina. Neuroinflammation can activate microglia and trigger reactive astrogliosis, leading to inflammatory cascades, neurotransmitter imbalances, and ion channel dysfunction. Conclusion: We have presented rare cases of epilepsy as an IC of pansinusitis, highlighting the need for thorough evaluations in epilepsy patients without known intracranial infections, including investigations for other potential infectious sources.